Increase in treatment compliance reveals new options of treatment of gastroesophageal reflux disease - Yu. V. Yevsyutina; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To present update on the causes of insufficient treatment response to proton pump inhibitors (PPI) at gastroesophageal reflux disease (GERD) and to inform on the options of increasing patients’ compliance.Summary. Decline of treatment compliance remains to be one of the principal causes of refractory course of gastroesophageal reflux disease. Existing PPIs have some limitations — necessity of intake strictly before meal and short action period. Dexlansoprazole in double delayed release form allows intake without relation to food intake that allows to increase compliance to treatment.Conclusion. The wide prevalence of GERD dictates necessity of search of new effective agents. Thus one of the principal causes of refractory course of disease is decreased adherence to treatment. Application of new PPI i.e. dexlansoprazole with once per day intake will allow to increase compliance to treatment and to reduce frequency and intensity of symptoms both at erosive esophagitis and non-erosive reflux disease.